Transformasi Model Pembelajaran dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam (PAI): Studi Kasus di SMA Al Muslim Sidoarjo - Maulidi, Rizki; Badriyah, Laila; Masnawati, Eli (ISLAMIKA, 2024)
This research aims to determine the transformation of learning models in improving the quality of Islamic religious education (PAI) learning at SMA Al Muslim Sidoarjo. This research uses a qualitative descriptive method with a case study approach. Data collection techniques in this research are through observation, interviews and documentation. Data analysis techniques are carried out through data collection, data reduction, data presentation, and drawing conclusions. Data validity using triangulation techniques. The results of the research show that the transformation of the learning model at SMA Al Muslim Sidoarjo is done by supervising and improving facilities in the form of facilities and infrastructure from school management. Efforts to improve the quality of PAI learning through transformation of the learning model are carried out by looking at teacher competency and monitoring the school principal as well as full support from school management. Supporting factors for the transformation of the learning model are developing digital skills and applying religious moral values, monitoring students' academic progress through the My Al Muslim application and discussing to find joint solutions to improve learning and IT infrastructure in addition to providing school internet. Meanwhile, the inhibiting factor is the challenge of teacher consistency in continuing to adapt to digital learning models that are always up-to-date. In the future, schools are expected to continue to innovate learning and evaluate inhibiting factors so that the delivery of material from teachers to students becomes more competent.